2019
DOI: 10.1007/s00167-019-05400-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative graft-related complications are a risk factor for recurrence in arthroscopic Latarjet stabilisation

Abstract: PurposeThe goal of this study was to evaluate clinical and radiological outcomes after arthroscopic Latarjet stabilisation in anterior shoulder instability.MethodsNinety-three patients after primary arthroscopic Latarjet stabilisation were reviewed. Satisfaction, subjective shoulder value (SSV), Walch–Duplay and Rowe scores, and range of motion and stability were evaluated on clinical examination. Computed tomography (CT) was used to analyse graft position and fusion.ResultsNinety patients (96.8%) were availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 51 publications
3
19
1
1
Order By: Relevance
“…Although soft-tissue dissection is reduced by the arthroscopic approach, graft positioning and intraoperative complications are still a source of concern. 4 Kordasiewicz et al reported a correct position of the graft in the axial plane in 40.5% of patients and in the sagittal plane (between 3 and 5 o'clock) in 54.6% of cases.…”
Section: See Related Article On Page 3221mentioning
confidence: 95%
“…Although soft-tissue dissection is reduced by the arthroscopic approach, graft positioning and intraoperative complications are still a source of concern. 4 Kordasiewicz et al reported a correct position of the graft in the axial plane in 40.5% of patients and in the sagittal plane (between 3 and 5 o'clock) in 54.6% of cases.…”
Section: See Related Article On Page 3221mentioning
confidence: 95%
“…high complication rates, including pain due to soft-tissue impingements [17], neurologic impairments, and bone-block nonunion or malposition [11,13,15,18,25,39].…”
Section: Introductionmentioning
confidence: 99%
“…The Latarjet technique is a bone‐block procedure that gained considerable popularity in recent years, as it proved effective at preventing recurrent dislocations [2, 8, 19], while allowing rapid recovery and return to play (RTP) [3, 8, 19, 23]. The Latarjet procedure has also demonstrated satisfactory long‐term outcomes in young recreational and competitive athletes [5, 13, 20, 41], despite comparatively high complication rates, including pain due to soft‐tissue impingements [17], neurologic impairments, and bone‐block nonunion or malposition [11, 13, 15, 18, 25, 39].…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 20 While the risk is still relatively low and the procedures are generally considered safe, complications with operative management can include, but are not limited to, infection, nerve injury, graft malposition, graft nonunion, and recurrent subluxation/dislocation. 9 , 16 , 17 , 21 , 22 , 26 , 31 , 35 , 40 Through this study, the authors are interested in specifically analyzing the perioperative complications associated with instability repair procedures by utilizing the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) registry. While previous studies have utilized the NSQIP database for similar outcome measures, the cohort of patients utilized in those analyses was limited by the availability of data at the time of publication.…”
mentioning
confidence: 99%